Exploring Teachers Knowledge of Classroom Management and Control - Ayebo, Abraham; Assuah, Charles (Universiti Utara Malaysia Press, 2017)
Purpose - This paper presents the results of a study that sought to determine teacher conceptions of classroom management and control. The study explored classroom management knowledge of participants, and how the knowledge was gained. It also investigated the extent to which participants held various conceptions, including rule-based, dominance and nurturance conceptions, about how teachers established and maintained classroom control.